TRHUMIDADE - A water diffusivity model to predict moisture content profiles. Issue 1 (1st January 2018) - Guimarães, A.S.; Ribeiro, I.M.; Freitas, T.S.
Abstract: The study of moisture transfer in porous building materials after a long contact with liquid water is crucial to prevent damages, in particular, when it comes to extreme rain events or floodings. Several experimental techniques are available to measure the moisture content evolution during water absorption tests, although the great majority of them are time-consuming and require expensive equipment. For this reason, the use of validated hygrothermal simulation tools is essential for a faster analysis without losing accuracy. The main goal of this paper is to compare the simulated moisture content profiles provided by the program TRHUMIDADE with those obtained by the gamma-ray attenuation method and by WUFI program. In TRHUMIDADE the heat and moisture phenomenon is described by the moisture content gradient, which may be more appropriate in predicting scenarios involving liquid water transport. The obtained results showed a good agreement for the red-brick and the autoclaved cellular concrete, which contributes to validate the future use of the program in the development of advanced hygrothermic studies in multi-layered building walls.